Reply to George S. Ford’s ‘A Counterfactual Impact Analysis of Fair Use Policy on Copyright Related Industries in Singapore: A Critical Review’ - Roya Ghafele (Laws, 2020)
Ford’s ‘Comments (Laws 2018, 7(4), 34; https://doi.org/10.3390/laws7040034, https://www.mdpi.com/2075-471X/7/4/34)’ are biased by a partisan approach to the issues at stake and cannot be based on scientific evidence. The article “A Counterfactual Impact Analysis of Fair Use Policy on Copyright Related Industries in Singapore”, which Gibert and Gafelle wrote together nearly a decade ago, came under heavy criticism by George S. Ford from an organization named the Phoenix Centre for Advanced Legal and Economic Public Policy Studies in an article ‘A Counterfactual Impact Analysis of Fair Use Policy on Copyright Related Industries in Singapore: A Critical Review’. (subsequently ‘the fair use study’) The Fair use study was peer reviewed by LAWS and supports the hypothesis that a more flexible fair use policy is correlated with faster growth rates in private copying technology industries and fewer negative consequences than copyright holders may desire to see. The findings of the Fair use study upset Ford as well as a host of different institutions advocating for copyright owners, such as International Federation of Reproduction Rights Organizations; Motion Picture Association; Publishers Association of Australia; New Zealand Society of Authors or Recorded Music NZ-RMNZ. Ford’s article, however, neither contains novel research, nor is it an effort to update this fairly dated analysis, which reflects data nearly twenty years of age. Rather, it is an unnecessary duplication of an old analysis with only some minor modifications, which serve to show that fair use is actually not beneficial to the economy. At the end of this peculiar exercise, Ford himself admits that this analysis is meaningless. The rest of Ford’s article consists of discussing potential limitations of the Fair use study, in a manner which suggests the authors had never disclosed them (which however they had) and thus is misleading. Ford’s most fundamental point of criticism is hinged on a supposed lack of evidence regarding the parallelism assumption, which he himself admits is impossible to offer. Contrary to Ford’s analysis, the Fair use study has the merit of being fully reproducible, which is not the case for Ford’s article. Also, contrary to Ford’s article, the Fair use study has the advantage of carefully drafted limitations and of offering genuine research insights.